2-phenylethanol (rose aroma) production potential of an isolated pichia kudriavzevii through solid-state fermentation. (June 2020) - Martínez-Avila, Oscar; Sánchez, Antoni; Font, Xavier; Barrena, Raquel
Graphical abstract: Highlights: A new 2-phenylethanol (2-PE) producer yeast was isolated and identified as P. kudriavzevii. Compared to other yeast, the isolated P. kudriavzevii produces up to 70 % more 2-PE. 2-phenylethanol production via solid-state fermentation was optimized in batch mode. Temperature and initial moisture content significantly affected the 2-PE production. Maximum 2-PE level was 27.2 mg per g of dry matter at 31 °C and 76 % moisture content. Abstract: 2-phenylethanol (2-PE) is a higher alcohol widely used in industry that can be obtained by solid-state fermentation (SSF) using low-cost raw materials. This report describes the 2-PE production potential of an indigenous Pichia kudriavzevii isolated from solid-state fermented sugarcane bagasse that possesses attractive characteristics for processing waste streams such as its low-pH tolerance, high growth rate and temperature resistance. Besides, 2-PE production was optimized in batch-SSF using sugarcane bagasse supplemented with l -phenylalanine as substrate. Full factorial design allowed identifying the pH adjustment, micronutrient addition, inoculum and co-substrate load effects, and response surface methodology served to identify the maximum production based on temperature, initial moisture content (MC0 ) and specific airflow rate (SAFR ). While the pH adjustment and micronutrient addition did not affect the 2-PE production, temperature and MC0 resulted critical for the process. After optimization, the maximum 2-PE content was 27.2 ± 0.2 mg per gram of dry substrate at 31 °C, 76 % MC0 and 0.129 L h −1 g −1 SAFR . This result was 23.8 % higher than the sub-optimal condition, and it is the highest 2-PE production via SSF reported so far. These results confirm the ability of P. kudriavzevii for producing 2-PE, and its potential for using waste streams as substrate.